Country in the city : agricultural functions of protohistoric urban settlements (Aegean and Western Mediterranean) - Garcia, Dominique,; Orgeolet, Raphael,; Pomadère, Maia,; Zurbach, Julien, (Archaeopress archaeology., 2019)
Assembles contributions on the place of agricultural and Early Iron Age Mediterranean, concentrating on the second-millennium Aegean and the protohistoric north-western Mediterranean.